"Degradabilidad in situ del ensilaje del pasto seboya (Panicum máximum Jacq) con diferentes niveles de rechazo de piña )ananas comossus)" - Montenegro Holguín, Jhon Bolívar (2016)
This research was conducted at the Experimental Farm "La Maria" State Technical University of Quevedo, in Rumiología Laboratory of the Faculty of Animal Science, located at km 71/2 via Quevedo. The objectives were to evaluate the in situ grass silage Savoie (Panicum maximum Jacq), associated with different levels of rejection of pineapple (Ananas comosus) digestibility. For the present study an experimental design of randomized complete block where seven incubation times (0, 3, 6, 12, 24, 48 and 72 hours) were evaluated employment. S fistulated cattle and use four, each bovine was used as a criterion block where the degradability of each sample was evaluated. By using the statistical package SAS version 9.0 and differences between treatments they were compared using the Tukey test (p ≤ 0.05). The best performance was presented rejection treatment 2 pineapple obtained the best percentages of digestibility (91.17%), after 72 hours of incubation ruminal digestibility best observed at 72 hours (p ≤ 0.05) with higher digestibility percentages for the T6 treatment (60% and savoy rejection of 40% pineapple grass), presented higher digestibility values at 48 hours (54.58) and 72 hours (62.64), there was no statistical difference ( p ≤ 0.05) between treatments, behaving better treatments 2 and 6 with high percentage of digestibility. Rejecting the reduc Pineapple 100% higher data reported in all incubation times unlike other treatments under study. Keywords: products, ruminal digestibility in situ, rejection of pineapple, Pasto Savoie